Organelle Studies and Proteome Analyses of Mitochondria and Plastids Fractions from the Diatom Thalassiosira pseudonana - Schober, Alexander F; Rï O Bï Rtulos, Carolina; Bischoff, Annsophie; Lepetit, Bernard; Gruber, Ansgar; Kroth, Peter G (Plant & cell physiology, 2019)
Diatoms are unicellular algae and evolved by secondary endosymbiosis, a process in which a red alga-like eukaryote was engulfed by a heterotrophic eukaryotic cell. This gave rise to plastids of remarkable complex architecture and ultrastructure that require elaborate protein importing, trafficking, signaling and intracellular cross-talk pathways. Studying both plastids and mitochondria and their distinctive physiological pathways in organello may greatly contribute to our understanding of photosynthesis, mitochondrial respiration and diatom evolution. The isolation of such complex organelles, however, is still demanding, and existing protocols are either limited to a few species (for plastids) or have not been reported for diatoms so far (for mitochondria). In this work, we present the first isolation protocol for mitochondria from the model diatom Thalassiosira pseudonana. Apart from that, we extended the protocol so that it is also applicable for the purification of a high-quality plastids fraction, and provide detailed structural and physiological characterizations of the resulting organelles. Isolated mitochondria were structurally intact, showed clear evidence of mitochondrial respiration, but the fractions still contained residual cell fragments. In contrast, plastid isolates were virtually free of cellular contaminants, featured structurally preserved thylakoids performing electron transport, but lost most of their stromal components as concluded from Western blots and mass spectrometry. Liquid chromatography electrospray-ionization mass spectrometry studies on mitochondria and thylakoids, moreover, allowed detailed proteome analyses which resulted in extensive proteome maps for both plastids and mitochondria thus helping us to broaden our understanding of organelle metabolism and functionality in diatoms.
Keywords: Thylakoids; Plastids; Chloroplast; Proteome; mitochondrie; Diatoms; Organelle isolation; Proteomics; Photosynthesis; plastidy; tylakoidy; Mitochondria; proteom; Respiration; rozsivky